0152 Caffeine Use And Sleep In U.S. Hispanic/Latinos: Findings From HCHS/SOL Sueño Ancillary Study. (27th April 2018) - Ogilvie, R P; Simonelli, G; Sotres-Alvarez, D; St-Onge, M; Mossavar-Rahmani, Y; Perreira, K; Petrov, M; Kim, Y; Balkin, T; Wallace, D; Reid, K J; Daviglus, M; et al.
Abstract: Introduction: Caffeine has biologic effects on sleep and those with poor sleep commonly use caffeine to mitigate daytime consequences. The relationship between caffeine consumption and sleep has not been studied in U.S. Hispanics/Latinos. Methods: We examined cross-sectional associations between caffeine consumption and sleep, using data from adults aged 18–64 years in the Hispanic Community Health Study/Study of Latinos Sueño Ancillary Study (2010–2013). Habitual caffeine consumption was measured in cups using the sum of four questions on coffee, tea, caffeinated soda, and energy drink consumption, and high caffeine consumption was defined as ≥4 cups per day. One week of actigraphy was used to calculate sleep duration, sleep efficiency, sleep fragmentation index, and interdaily stability. Other sleep measures included the Epworth Sleepiness Scale (ESS), the Insomnia Severity Index (ISI), self-reported use of sleep aids, and apnea-hypopnea index (AHI) via home sleep apnea monitor. Descriptive means and proportions by caffeine consumption accounted for the complex survey design and were age and sex standardized based on the 2010 U.S. Census. Results: Among 2, 205 participants (mean age 40.7 ± 12.9, 51.8% female), age- and sex-standardized mean caffeine consumption was 2.3 cups per day, and 20.0% had high caffeine consumption. Compared to caffeine non-users, those with high caffeine consumption had 2.0% lower sleep efficiency (95%CI [0.9–3.0]) and 1.9% higher sleep fragmentation index (95% CI [0.6–3.2]), while no significant difference was observed in sleep duration or interdaily stability. A greater proportion of high caffeine consumers versus non-users had ESS ≥ 11 (19.3% vs 11.4%), ISI ≥ 15 (27.0% vs 14.8%), and sleep aid use (28.9% vs 16.2%), while sleep apnea prevalence was similar (6.5% vs 4.6%). Conclusion: In a cohort of working age Hispanic/Latino adults, high caffeine consumption was associated with reduced sleep efficiency and greater sleep symptoms. Support (If Any): This work was supported by HL007779, HL127307, and HL098297. HCHS/SOL was supported by NIH contracts to the University of North Carolina (N01HC65233), University of Miami (N01HC65234), Albert Einstein College of Medicine (N01HC65235), Northwestern University (N01HC65236), and San Diego State University (N01HC65237).